2020
DOI: 10.1002/hon.2772
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine release syndrome after allogeneic stem cell transplantation with posttransplant cyclophosphamide

Abstract: Cytokine release syndrome (CRS) is a systemic inflammatory response with aberrant immune activation and immune hyperstimulation, that leads to increased cytokine levels and inflammation. CRS has been described after antibody and cellular-based therapies. The use of posttransplant cyclophosphamide (PTCy) as graft-vs-host disease (GVHD) prophylaxis in haploidentical hematopoietic stem cell transplantation (haplo-HSCT) has led to the extension of allogeneic HSCT to patients without HLA-identical donors. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
2
14
1
Order By: Relevance
“…They need facemask with oxygen delivered at > 6 L/minute to overcome the oxygenation deficit. In our study, the incidence of CRS was 54.9%, which was markedly lower than prior reports [15,16,28,29,32]. The biggest difference was the use of ATG instead of PTCy for GVHD prophylaxis between our study with others.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…They need facemask with oxygen delivered at > 6 L/minute to overcome the oxygenation deficit. In our study, the incidence of CRS was 54.9%, which was markedly lower than prior reports [15,16,28,29,32]. The biggest difference was the use of ATG instead of PTCy for GVHD prophylaxis between our study with others.…”
Section: Discussioncontrasting
confidence: 80%
“…We speculated that this might be due to the continuous expansion of T-cells after the reinfusion of stem cells around d+7. Many studies showed similar results demonstrating that the use of peripheral blood grafts was an independent factor predictive of CRS development after haplo-HCT [29,32,37]. In our series, the source of grafts consisted of PB and PB + BM.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Grade 2 ( Table 6 ) has been defined as hypotension that can be handled with fluid or only low-dose treatment with one vasopressor, mild respiratory symptoms responsive to low-flow oxygen, or Grade 2 organ involvement [ 73 ]. Patients with Grade 2 should be considered for immunosuppressive treatment, whereas patients with Grade 3 or more should receive immediate treatment [ 81 ]. The decision whether to start with immunosuppressive treatment should probably be based on a general clinical evaluation, and immunosuppression should be started early especially for elderly patients and patients with comorbidities who are judged not to be able to tolerate the altered hemodynamics and/or organ involvement associated with the syndrome.…”
Section: Treatmentmentioning
confidence: 99%